Utilizing MBTI to Enhance Career Fit for Information Technology Students - Mualim, Wildan; Roji, M. Fatkhur; Astrella, Nathania Bayu (Universitas Nurul Jadid, 2026)
A significant challenge faced by students in Information Technology (IT) programs is the mismatch between their personality traits and career paths. Many students struggle to determine the right career trajectory in the IT industry, often choosing based on market trends or peer influence rather than considering the alignment of their personality with job requirements. The lack of a psychometric-based counseling system to help align personality with career choices further exacerbates this issue. This study aims to explore the effectiveness of using the Myers-Briggs Type Indicator (MBTI) to align students' personalities with their career preferences. The research was conducted with a sample of 80 final-year students from the Information Technology and Systems program at Yadika Institute of Technology and Business Pasuruan. The findings revealed that the majority of students exhibited introverted personality traits, with INFP and INTP being the most common types. A statistically significant correlation was found between MBTI types and preferred career fields. For instance, students with INFP and INTP types leaned toward creative and analytical professions such as UI/UX design, software engineering, and data science, while ESTJ types favored managerial roles. Additionally, 73% of students reported high satisfaction with the career recommendations provided based on their MBTI results. This research supports the use of MBTI as an effective tool for career counseling, offering a more personalized approach to career decision-making.